Analysing the Prevention of Terrorism Act 2015 in combating terrorism in Malaysia - Faris Danie; Asri Shamsul; Hafiz Hafizi; Aiman Farhan; Adliesyamil (Penerbit Universiti Kebangsaan Malaysia, 2023)
Combating terrorism and violence has been a global challenge that alerted many world leaders, and Malaysia has actively participated in preventing the threats in a variety of methods and mechanisms. In the effort to preserve the security of the country and its people, Malaysia had introduced the Prevention of Terrorism Act (POTA). The genesis of the formation and legislation of POTA is based on the increasing trend of terrorism attacks around the globe, which finally affected the security of the world countries. Internationally, the 11 September 2001 tragedy had been a turning and changing point for the world to emphasise new mechanisms of combating and preventing terrorism in this country. In Malaysia, the existence of terrorism groups such as Jemaah Islamiyah that originated from Indonesia and some local extremist groups are needing a fresh approach of comprehensive legal framework to combat the terrorism effectively. This issue is very important to be addressed as terrorism is seen as threat to national security and it may impact negatively on the peace and harmony of a state.